Convertible debt issuance, capital structure change and financing-related information - Dann, Larry Y.; Mikkelson, Wayne H. (Journal of Financial Economics, 1984)
This paper provides evidence on the valuation effects of convertible debt issuance. Common stockholders earn significant negative abnormal returns at the initial announcement of a convertible debt offering, and also at the issuance date. In contrast, the average valuation effect on common stock at the announcement of non-convertible debt offerings is only marginally negative, and is zero at issuance. The significant negative average effect on common stock value appears not to be systematically related to either the degree of leverage change induced by the convertible debt issuance or the extent to which the proceeds from issuance are used for new investment or to refinance existing debt. If, as appears likely, the issuance of convertible debt on average increases financial leverage, these results are inconsistent with evidence from other recent studies documenting common stock price effects of the same sign as the change in leverage. The evidence suggests that convertible debt offerings convey unfavorable information about the issuing firms, but the specific nature of such information remains unidentified.